Multi-wave seismic sedimentology in geological anomaly characterization: methodological innovations and case applications - Dai, Juncheng; Lv, Wenzheng; Wei, Wei; Yan, YuanYuan; Luo, Bin; Ran, Qi; Chen, Kang; Wang, Yifei (Frontiers in Earth Science, 2025)
With the increasing demand for unconventional resources, accurate characterization of tight sandstone gas reservoirs has become crucial. This study introduces an innovative multi-wave seismic sedimentology approach integrating P-wave, converted S-wave (PS-wave), and pseudo-S-wave attributes to enhance lithological prediction and reservoir heterogeneity analysis in the Jurassic Shaximiao Formation, Sichuan Basin. By combining 90° phase rotation, high-frequency stratal slicing, and differential PP- and PS-wave amplitude and phase analysis, the workflow effectively resolves vertically stacked sand bodies and identifies high-porosity “sweet spots.” Results demonstrate that PS-wave data provide stable polarity responses for lithology discrimination, while pseudo-S-wave attributes improve vertical resolution for multi-phase channel identification. Field validations confirm >90% accuracy in sand body geometry predictions, with horizontal drilling achieving 87% reservoir encounter rates. The methodology overcomes limitations of conventional P-wave methods in low-impedance-contrast reservoirs and offers a cost-effective solution for early-phase exploration with limited well data. This integrated approach advances tight gas exploration by enabling robust characterization of complex geological anomalies and heterogeneous systems.